Bioaccumulation of Heavy Metals in Clarias gariepinus and Oreochromis spirulus niger from Masinga Reservoir, Kenya - Nzeve, Julius K.; Njuguna, S. G.; Kitur, E. C. (IOSR Journal of Environmental Science, Toxicology and Food Technology, 2014)
The pollution of aquatic ecosystems with heavy metals has become a worldwide concern. This is because of their ability to bioaccumulate in aquatic organisms and especially in fish which is a source of livelihood for human populations. Therefore, an assessment of heavy metal contamination (Cu, Zn, Pb, Cr and Mn) in two selected food fish species, Clarias gariepinus and Oreochromis spirulus niger in Masinga reservoir was carried out between January 2013 and December 2013. Heavy metal Concentrations were determined using atomic absorption spectrophotometer. The data obtained was analyzed using one way analysis of variance and significant differences accepted at p ≤ 0.05. Post Hoc Turkeys’ test was used to separate means. In Clarias gariepinus, mean metal concentrations (mg/kg) in muscles were Cu (0.677 – 0.974), Zn (32.929 – 37.205), Pb (0.643 – 1.078), Cr (0.516 – 0.858) and Mn (0.452 – 0.990). Pb exhibited a significance difference between the sites (p < 0.05). Mean values for heavy metals in Oreochromis spirulus niger (mg/kg) for different sites were Cu (0.515 – 0.782), Zn (29.645 – 37.999), Pb (0.552 – 0.765), Cr (0.559 – 0.791) and Mn (0.183 – 1.480). Only Mn showed significant differences between the sites (p < 0.05). Heavy metal concentrations in the two fish species were lower than World Health Organization (WHO) set limit except for Cr. Results from this study demonstrate the need for an ecosystem approach towards sustainable management of reservoirs. This will curb aquatic pollution which is a health risk for people consuming aquatic resources contaminated with heavy metals
Keywords: Heavy metals; Bioaccumulation; Pollution; Fish; Masinga reservoir